The Concept of Manners and Its Relation to Academic Ethics - Nur Alfiyah Nasywa; Endrew Albariq Pinem; Rizky Ramadhani; Hamdani Hasibuan (ISNU Nine-Star Multidisciplinary Journal, 2025)
In this study, the author applies a library research method. Data sources can only be obtained from libraries or other written documents, including journals, books, and other literature. Adab and academic ethics are closely related. Both have the same meaning and purpose. Adab are rules of etiquette based on religious principles. Academic ethics are moral guidelines that must be followed by everyone in an educational environment. This paper demonstrates that adab and academic ethics are crucial in creating a positive and productive learning environment. Understanding the concept of adab is expected to improve integrity and discipline in education, which will shape better individual character. This study also shows that adab can influence how we behave in the academic world